Fiber fluorescent spectroscopy - Beres-Pawlik, Elzbieta Maria; Stawska, Hanna; Śliwa, Mariusz; Sokół, Wojciech; Kulas, Zbigniew; Kłonowski, Łukasz; Popenda, Maciej; Kochanowicz, Marcin; Żmojda, Jacek; Dorosz, Dominik (Photonics Letters of Poland, 2014)
<!– saved from url=(0022)http://internet.e-mail –> In this paper we present the current history of fluorescent spectroscopy research conducted in our team. Results obtained by single-photon fluorescence spectroscopy are presented, together with a description of potential PCF fiber solutions for multi-photon type of excitation. Single-photon research contained of two methods – the classical endoscope imaging as well as fluorescence lifetime analysis. The proposed PCF fibers are optimized for possible use as a fluorescent sensors, which will require the usage of femtosecond light pulses. Full Text: PDF References Z. Kulas, E. Bereś – Pawlik, T. Kręcicki, SPIE – cop., 59590 (2005) E. Bereś – Pawlik, A. Grobelny, Z. Pałasz, T. Kręcicki, Polish Patent PL 207002 (2010) Z. Kulas, E. Bereś – Pawlik, T. Kręcicki,"Numerical analysis of endoscopic autofluorescence imaging for cancerous tissue detection", J. Non-Cryst Solids 32, 2468-2475 (2006) CrossRef E. Bereś – Pawlik, A. Grobelny, Z. Pałasz, T. Kręcicki, Polish Patent PL 207002 (2010) Z. Kulas, PhD Thesis, I28/2012/P-002, Wroclaw University of Technology (2012) U. S. Dinish, P. Gulati, V. M. Murukeshan, L. K. Seah, "Diagnosis of colon cancer using frequency domain fluorescence imaging technique", Optics Communications 271, 291-301 (2006) CrossRef F. V. Bright, Ch. A. Munson, "Time-resolved fluorescence spectroscopy for illuminating complex systems", Analytica Chimica Acta 500, 71-104 (2003) CrossRef Gyungseok Oh, Euiheon Chung, Seok H. Yun, "Optical fibers for high-resolution in vivo microendoscopic fluorescence imaging", Optical Fiber Technology 19, 760-771 (2013) CrossRef E. Bereś – Pawlik, K. Gąsiorek, Z. Kulas, M. Rząca, "Optical Fiber Sensors for Point Investigation οf Cancer Tissues ", Acta Physica Polonica A 116, 254-256 (2009) DirectLink K. Gąsiorek, M.S. Thesis, Wrocław University of Technology (2006) W. Sokół, M.S. Thesis, Wroclaw University of Technology (2013) B. B. Collier, M. J. McShane, "Time-resolved measurements of luminescence", Journal of Luminescence 144, 180-190 (2013) CrossRef T. Dou et al., "Dispersion control with reflection grisms of an ultra-broadband spectrum approaching a full octave", Opt. Express 18, 27900-27909 (2010) CrossRef S. F. Elahi, T. D. Wang, "Future and advances in endoscopy", J. Biophotonics. 4, 471–481 (2011). CrossRef H. Stawska, E. Bereś-Pawlik, Dispersion properties of double-clad hollow-core photonic bandgap fibers based on a circular lattice cladding, in Proc. 22nd International Conference on Optical Fiber Sensors, OFS-22, 84217F-1 – 84217F-4 (15-19 Oct. 2012, Beijing, China) E. Bereś-Pawlik, H. Stawska, Ł. Kłonowski, Detecting cancerous tissues in human body by means of fiber fluorescent spectroscopy, ICTON (2013)